Accent in digital humanities and language studies: the case in Hong Kong - Lam, Charles; Wong, Catherine (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper argues for the importance of the awareness of “DH accent” and demonstrates with examples in English studies how a localised variation of the curriculum facilitates students’ learning in the classroom and at the curriculum level. This study identifies the problem that studies in digital humanities have focused on the Anglo-American world. We demonstrate with an example in the Hong Kong context that even a curriculum of English language studies requires adaptation for the local needs, such as focus on second language learning and knowledge of contrastive grammar with the local language. To achieve these goals, instructors integrate materials that are tailored for students of language studies, who are typically proficient in humanistic argumentation and concepts but less fluent in digital skills. Use cases in teaching and examples of student projects are shown to illustrate the outcome of learning. The study presents important educational implication and direction for future research and education of the digital humanities.